2015
DOI: 10.1002/atr.1329
|View full text |Cite
|
Sign up to set email alerts
|

The effects of on‐street parking on the service rate of nearby intersections

Abstract: Summary An on‐street parking maneuver can often start a temporary bottleneck, leading to additional delay endured by the following vehicles. If the maneuver occurs near a signalized intersection, the service rate of the intersection might be reduced. In this paper, a model is built to analyze the effects of parking maneuvers on the intersection service rate. Based on the hydrodynamic theory of traffic flow, the perturbation caused by the parking maneuver is analyzed. Using dimensional analysis, we illustrate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 16 publications
1
14
0
Order By: Relevance
“…Other researchers have evaluated the traffic effects of parking maneuvers [24,25]. They have proposed a model to analyze the impact of parking maneuvers on a road segment and their influence on the capacity of nearby intersections and the overall network.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other researchers have evaluated the traffic effects of parking maneuvers [24,25]. They have proposed a model to analyze the impact of parking maneuvers on a road segment and their influence on the capacity of nearby intersections and the overall network.…”
Section: Literature Reviewmentioning
confidence: 99%
“…= equation. In this section, the reduction in service rate caused by an upstream parking maneuver and calculated earlier is compared with that caused by a downstream parking maneuver at a distance l d from Cao et al (8).…”
Section: Table 1 Road Map To Equations By Conditionmentioning
confidence: 99%
“…Some studies have also focused on other externalities of on-street parking such as the interactions between parking and traffic performance (7). Cao et al looked at the reduction of intersection service rate caused by on-street parking maneuvers but only when the parking maneuvers happened downstream of the inter section (8). They found that the distance between the parking location and the intersection was highly influential to the performance of the intersection.…”
mentioning
confidence: 99%
“…Therefore, many motorists park their vehicles on street [1]. On-street parking had caused the reduction of road capacity [2], traffic conflict [3], traffic delay [4], and deterioration of traffic performance [5,6,7,8].…”
Section: Introductionmentioning
confidence: 99%